2016
DOI: 10.1186/s12879-016-1508-0
|View full text |Cite
|
Sign up to set email alerts
|

Sero-epidemiological assessment of Chlamydia trachomatis infection and sub-fertility in Samoan women

Abstract: BackgroundIn our recent village-based cross-sectional study, the prevalence of nucleic acid amplification technique (NAAT) diagnosed Chlamydia trachomatis (CT) in sexually active Samoan women was very high (36 %), and test positivity was associated with sub-fertility. We conducted a serological and epidemiological analysis in these participants to identify if serological data can provide further insight into the potential contribution of CT to sub-fertility in this population.MethodsSerological prediction of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
0
24
1
1
Order By: Relevance
“…Microscopic intraluminal damage of the mucosa may also impair the ability to conceive Keltz et al 2013;Menon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic intraluminal damage of the mucosa may also impair the ability to conceive Keltz et al 2013;Menon et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several ELISA assays have been commercially developed with Chlamydia antigens; some of them are known to be C. trachomatis-specific. Menon et al (2016) reported that CT-IgG ELISA-plus MEDAC assay (uses a synthetic peptide of a variable domain from an immunodominant region of the MOMP), as a serological test of C. trachomatis, significantly associated sub-fertility, with 50% of infertile women being positive. Land et al (2003) observed a sensitivity and specificity of 55 and 83%, respectively, for the MEDAC test, while the ELISA Labsystems assay showed a sensitivity and specificity of 37 and 87%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA for detection of chlamydial antibodies in clinical specimens using C. trachomatis MOMP has been studied extensively as a screening tool and has been reported to have good performance when compared with the gold standard [9,[26][27][29][30][31][32] . Thus, the affordability, easy application and high throughput of the immunoassay, makes it a practical screening tool in regions of high C trachomatis prevalence and a good substitution for the more sensitive and specific PCR especially low-income countries.…”
Section: Discussionmentioning
confidence: 99%